The Value of Traditional Social Education "Bukak Luwur Sunan Kudus" - Falaq, Yusuf (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study examines the value of traditional social education "Bukak Luwur Sunan Kudus". In particular, this research is aimed at uncovering the meaning of the tradition of “Bukak Luwur Sunan Kudus”; the peculiarities of the tradition of “Bukak Luwur Sunan Kudus”; and the value of social education contained in the "Bukak Luwur Sunan Kudus" tradition. The qualitative approach was chosen as a way to reveal the tradition of “Bukak Luwur Sunan Kudus”. As for the results of this study, the meaning of the social tradition of "Bukak Luwur Sunan Kudus" starts from replacing the mosquito net in the area of ​​Sunan Kudus's tomb, the traditional social event "Bukak Luwur Sunan Kudus" an effort to pray for, respect, imitate the teachings and seek blessings from Sunan Holy. For the Kudus community, the implementation of Bukak Luwur” is considered an obligation. The peculiarity of the "Bukak Luwur Sunan Kudus" tradition is Ashura Porridge as a mandatory dish in the tradition. Meanwhile, the value of social education in the "Bukak Luwur Sunan Kudus" tradition includes: Social care values, responsibility values, mutual cooperation values, religious values, sharing values, gratitude values, values ​​of unity and integrity